Ocena kondycji upraw rolniczych objętych emisjami przemysłu hutniczego = Assessment of agricultural crops condition covered by emissions of metallurgy industry - Rosada, Janusz; Przewocka, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of conducted studies was to identify atypical diseases symptoms occurring in agricultural crops located in the area affected by industry (agricultural area covered by gas and dust emissions from Copper Smelter GŁOGÓW), as well as in crops grown on areas not influenced by antropopression (Lasocice near Leszno, Uścikowo near Oborniki Wlkp., Barcinek near Biskupice Wlkp.).
Keywords: uprawa rolnicza; czynniki abiotyczne; przemysł hutniczy; agricultural crops; abiotic factors; metallurgy industry